2003
DOI: 10.1177/03635465030310063201
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ankle Braces on the Prevention of Dynamic Forced Ankle Inversion

Abstract: This test holds promise for evaluating brace efficacy when landing with one foot unexpectedly on an object that acts to forcibly invert the ankle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 20 publications
1
37
0
1
Order By: Relevance
“…instrumentation A 7-camera, 240-Hz motion analysis system (Vicon Motion Systems and Peak Performance Inc, Oxford, UK) was used to obtain the 3-D kinematics during data collection. Anatomical reflective markers were used to define joint centers and placed at the left and right anterior superior iliac spines, superior iliac crests, posterior superior iliac spines, and greater trochanters, and right femoral epicondyle, right medial and lateral malleoli, and the right first and fifth metatarsal (eg, landing 21,25,32,33 and lateral cut 6,18,28 movements), during which ankle sprains typically occur. More recently, Cordova and colleagues 7 showed that a semirigid ankle brace is more effective in reducing rearfoot angular displacement and velocity than a lace-up brace, but the lace-up brace was more effective than no brace.…”
Section: Participants Amentioning
confidence: 99%
“…instrumentation A 7-camera, 240-Hz motion analysis system (Vicon Motion Systems and Peak Performance Inc, Oxford, UK) was used to obtain the 3-D kinematics during data collection. Anatomical reflective markers were used to define joint centers and placed at the left and right anterior superior iliac spines, superior iliac crests, posterior superior iliac spines, and greater trochanters, and right femoral epicondyle, right medial and lateral malleoli, and the right first and fifth metatarsal (eg, landing 21,25,32,33 and lateral cut 6,18,28 movements), during which ankle sprains typically occur. More recently, Cordova and colleagues 7 showed that a semirigid ankle brace is more effective in reducing rearfoot angular displacement and velocity than a lace-up brace, but the lace-up brace was more effective than no brace.…”
Section: Participants Amentioning
confidence: 99%
“…Hodgson et al 16 found that the maximum vertical ground reaction force (GRF) and loading rate at toe contact significantly increased and the ankle dorsiflexion angle at toe contact significantly decreased during the drop landing onto a flat surface wearing an ankle brace. In addition, Ubell et al 19 found that participants wearing semirigid braces had significantly greater success rates in keeping balance for 3 seconds after landing with a 24-degree inversion fulcrum affixed to the heel of the shoes, compared with a laceup brace and no brace. To date, no study has been conducted to compare the 2 testing protocols, landing on an IS and inversion drop. Therefore, it is important to examine differences and similarities of the 2 protocols and their implications in future testing of ankle braces and ankle performance mechanisms under these perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, it is quite important to ensure that proper personal protective equipment is used, instructions for usage are given, and that their maintenance is done. It has been reported that the usage of ankle braces reduce the traumas such as ankle sprain and ankle injuries which occur during landing [20]. The usage of personal protective equipment for the neck region should be considered in order to reduce the neck traumas.…”
Section: Photomentioning
confidence: 99%